FASILITAS PEMBELAJARANSEBAGAI STRATEGI PEMASARAN JASA PENDIDIKAN - Selly Jesika Rahmawati; Agus Timan; Ahmad Yusuf Sobri; Selly Jesika Rahmawati; Agus Timan (Universitas Negeri Malang, 2024)
Abstract: The objective of this research is to describe in detail the learning facilities at kindergarten Al- Falah Batu, the strategy for marketing educational services at kindergarten Al- Falah Batu, the use of learning facilities as a marketing strategy for educational services at kindergarten Al- Falah Batu, obstacles and the solution made in the use of learning facilities as a marketing strategy for educational services in kindergarten Al- Falah Batu. This research uses a qualitative research approach with descriptive research type. The results of this research are kindergarten Al- Falah Batu developed two types of learning facilities, namely indoor learning facilities and outdoor learning facilities, the educational services marketing strategy used by kindergarten Al- Falah Batu is called the service marketing mix concept. education (marketing mix) or 7P which is described through 7 elements including; (1) place, (2) promotion, (3) people, (4) process, (5) product, (6) price, (7) proof, the educational innovation developed by kindergarten Al- Falah Batu is in the form of aircraft classes, the inhibiting factor is that the community thinks that education at kindergarten Al- Falah Batu is expensive, and the location is too far from other districts. So that the solution to this problem is that the school provides discounts for students who are twins or students who are researching at kindergarten Al- Falah Batu and provided two cars that are willing to take students home to the farthest zone in Bumiaji, Batu City